Development of Pile Moored Sandwich Type Pontoon (P. M. S.) (Part 2) - Ohse, Shinichi; Matsumoto, Seiji; Kato, Hisao; Motono, Ichio; Ozasa, Hiroaki (PROCEEDINGS OF CIVIL ENGINEERING IN THE OCEAN, 1991)
The pile moored sandwich type pontoon is one of the newly developped pontoon for small to medium sized vessels, which enables smooth embarkation, disembarkation and cargo handling at any tidal lebel in sea areas with large tidal range. The authors installed this pontoon off the Port of Kanda, Fukuoka Pleft-lettecture and conducted field test. As a result, it was proved that the pile moored sandwich type pontoon could keep good conditions for cargo handling because of small pitching and rolling even in wavy conditions.